Polish Sinology – Reflection Paper - Góralczyk, Bogdan (Mongolian Journal of International Affairs, 2015)
This highly individual study is the first-ever attempt to describe Polish Sinology, Polish Sinologists and their individual choices, both vocational and social or political. The author, as an insider, uses interviews with some of the most important representatives of Polish Sinology (mainly of the older generation). He proposes individual systematization, fragmenting the history of the “real socialism” era (1950-1989) and after the democratic breakthrough of 1989 in many chapters, consisting of both collective and individual. Among the major findings is that the initial small circle of highly specialized individuals has recently been quickly growing, and so has the diversification within it. While until 1989 the career choices in this field were limited, basically an official (diplomatic or state bureaucratic) career was the only option, but after this threshold many new windows of opportunities were opened, which included for example personal choices like studying in Mainland China or Taiwan,, opening a business there, creating a website or even opening up a study center. Mongolian Journal of International Affairs Vol.19 2014: 87-115